The ASQ Certified Six Sigma Black Belt Handbook - McShane-Vaughn, Mary, 1963- (ASQ Excellence, 2022)
Fully updated to reflect the 2022 ASQ Certified Six Sigma Black Belt (CSSBB) Body of Knowledge (BoK), The ASQ Certified Six Sigma Black Belt Handbook, Fourth Edition is ideal for candidates studying for the CSSBB examination. This comprehensive reference focuses on the core areas of organization-wide planning and deployment, team management, and each of the DMAIC project phases. The fourth edition of this handbook offers thorough explanations of statistical concepts in a straightforward way. It also reflects the latest technology and applications of Six Sigma and lean tools. Updates you will find in the fourth edition include: • New topics and tools, such as return on investment calculations, the roles of coaching and finance in projects, process-decision program charts, interrelationship digraphs, A3 analysis, maturity models, key behavior indicators, and audit MSA • A new chapter on risk analysis and management • Revamped statistics sections • New tables, figures, and examples to help illustrate key points The ASQ Certified Six Sigma Black Belt Handbook, Fourth Edition is also a valuable addition to any quality practitioner's library.